2022
DOI: 10.1093/infdis/jiac183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Respiratory Syncytial Virus on Child, Caregiver, and Family Quality of Life in the United States: Systematic Literature Review and Analysis

Abstract: Background Respiratory syncytial virus (RSV), a leading cause of lower respiratory tract infection in US children, reduces quality of life (QOL) of children, their caregivers, and families. Methods We conducted a systematic literature review in PubMed, EconLit, and other databases in the United States of articles published since 2000, derived utility lost per RSV episode from cohort studies, and performed a systematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 34 publications
4
34
1
Order By: Relevance
“…Systematic literature reviews by Bowser et al [ 36 ] and Glaser et al [ 37 ] originally focused on an assessment of the cost of RSV-related illness and the burden of this outcome on US infant quality of life, respectively. The small number of resulting citations led to an expansion of the objectives to include systematic analyses.…”
Section: Health Economicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic literature reviews by Bowser et al [ 36 ] and Glaser et al [ 37 ] originally focused on an assessment of the cost of RSV-related illness and the burden of this outcome on US infant quality of life, respectively. The small number of resulting citations led to an expansion of the objectives to include systematic analyses.…”
Section: Health Economicsmentioning
confidence: 99%
“…Glaser et al [ 37 ] found that published data on the quality of life of US children with RSV were scarce and considered only premature hospitalized infants. Their review identified a key observational study that included follow-up data on both infants and caregivers.…”
Section: Health Economicsmentioning
confidence: 99%
“…We included all studies that reported RSV-related costs in US children aged 0 through 59 months published from 1 January 2014, through 2 August 2021. We then selected the literature focused on economic outcomes of RSV, separating the review of QOL for a separate submission [ 11 ]. Two reviewers (K.R.R.…”
Section: Methodsmentioning
confidence: 99%
“…No accounting of the burden of RSV disease is complete without an examination of its impact on the caregiver and the family taking care of the infant and on the direct and indirect costs to society. In this supplement, Glaser et al [ 30 ] assess the evidence on the impact of RSV on the quality of life of children under 5 years of age. They found 7 studies, only 2 of which were focused on preterm babies [ 31 , 32 ] and could be used to calculate the net quality-adjusted life years per nonfatal episode of RSV in the first 60 days of life.…”
mentioning
confidence: 99%